Studies on postharvest physiology and storage of bamboo shoots in Phyllostachys praecox f. preveynalis. - GU Qing; ZHU Mu-yuan; WANG Xiang-yang; PAN Jian-wei (浙江大学学报. 农业与生命科学版, 2002)
Fresh bamboo [Phyllostachys praecox f. preveynalis] shoots were harvested and stored at 4 C for 25 days after different treatments (O3, 0.05% carbendazol and 0.3% vitamin C+0.5% citric acid). All treatments gave better results than the control so far as the quality of stored bamboo shoots at the end of storage was considered, the ozone treatment being inferior to the others. Poly-phenol oxidase activity, cellulose and MDA level was markedly inhibited by the treatment. Due to fungal growth the shelf life of control bamboo shoots was reduced to less than 10 days. Microbial decay appeared to be the primary cause for deterioration in quality as shown by the development of bacterial, fungal and coliform microorganisms on external surfaces and internal tissues of bamboo shoots. Microorganisms were inhibited significantly by ozone in PVC bags. Bamboo shoots stored at 4 C after ozone treatment retained their initial quality and chemical components for about 25 days.